Effectiveness of Group Guidance with Group Investigation Learning Model to Develop Students' Assertiveness - Barida, Muya; Nurchairunnissa, Gefira; Saputra, Wahyu Nanda Eka; Setyowati, Aprilia; Ediyanto, Ediyanto; Atmoko, Adi (Jurnal Kajian Bimbingan dan Konseling, 2024)
Adolescents require assertiveness in socializing and interacting with their social environment in order to be able to express themselves well. However, there are still many adolescents who have not been able to express their thoughts, feelings, and hopes. This research aims to test the efficacy of group guidance services using the group investigation learning model to increase adolescent assertiveness. This research uses a one-group pretest-posttest research design to achieve the research objectives. The research subjects were six students at State Junior High School. The techniques and instruments used for data collection were an assertiveness scale. The assertiveness scale was tested for the level of validity and reliability through the Cronbach alpha formula. Furthermore, the data were analyzed using the Wilcoxon test. The results demonstrated a significant increase in student assertiveness after being given group guidance using the group investigation model. This indicates that the group investigation learning model is effective in increasing the assertiveness of adolescents.